2020
DOI: 10.2106/jbjs.rvw.20.00003
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Periprosthetic Distal Femoral Fractures After Total Knee Replacement

Abstract: » Periprosthetic distal femoral fracture after total knee arthroplasty carries substantial morbidity and mortality regardless of fixation technique.» Surgical treatment is favored in most patients compared with conservative therapy because of high rates of nonunion, malunion, and reoperation after casting or bracing.» Internal fixation techniques including retrograde intramedullary nailing and locked plating are favored for surgical treatment in most fractures when bone stock in the distal fragment allows for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…Their analysis, based on the French Society of Orthopedic Surgery and Traumatology (SoFCOT) classification [ 26 ], concluded that type B (fracture contact with keel or stem) has an especially poor prognosis. Periprosthetic femur fractures have been associated with substantial morbidity and mortality, regardless of fixation technique [ 27 ]. However, no consensus exists on whether plating or IM is a superior method of internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis, based on the French Society of Orthopedic Surgery and Traumatology (SoFCOT) classification [ 26 ], concluded that type B (fracture contact with keel or stem) has an especially poor prognosis. Periprosthetic femur fractures have been associated with substantial morbidity and mortality, regardless of fixation technique [ 27 ]. However, no consensus exists on whether plating or IM is a superior method of internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Supracondylar periprosthetic femoral fractures occur usually in geriatric populations [ 2 ] due to low velocity traumas such as a fall from standing height [ 3 ]. Osteoporotic and osteopenic bone is the major risk factors for such injuries [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…These fractures generally occur in the geriatric population aged above 60 years with associated osteopenic or osteoporotic bone quality [ 2 ]. Commonly, the fracture is secondary to minimal low-velocity trauma [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the balance between bone formation and bone resorption in osteoporotic patients is disrupted, thus resulting in poor osseointegration after prosthesis implantation ( Toepfer et al, 2021 ). So far, various conventional treatments have been attempted to increase the osseointegration of osteoporosis patients after joint replacement, but these treatments have not alleviated the problem ( Monotti et al, 2020 ; Quinzi et al, 2020 ). Postoperative systemic administration of antiresorptive drugs is limited by various side effects and low bioavailability that consistently achieves an unsatisfactory local osseointegration effect ( Frank et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%